Analisa Peramalan Jumlah Produksi Batako Pada Usaha Batako Papa Press Di Kota Ambon - Ditania Ditania; Ashwin Siahainenia; Febiola Matuankotta (Jurnal Administrasi Terapan, 2024)
Brick Papa Press has never done production forecasting since the establishment of the business until now, so when the company produces bricks, the number of existing brick demand decreases, while when the brick production company decreases, the existing demand increases. This study aims 1) to clearly find out the calculation of the production forecast of Batako Papa Press in the future 2) to help provide an overview for the company about the calculation of production forecast for the coming year. This research is a quantitative descriptive research, namely the author provides an overview of forecasting calculations for the future, while the method used here is by using linear trend analysis. The result of this discussion is the total brick production in 2021 as many as 10,455 bricks, in 2022 as many as 8,350 bricks and in 2023 as many as 6,245 bricks The conclusion of this writing is from calculations that have been carried out using the linear trend method, namely in 2021 as many as 10,455 bricks, in 2022 as many as 8,350 bricks, and in 2023 as many as 6,245 bricks. The standard error of estimation shows that the error rate in forecasting brick production is 3,065 bricks, so there is a possibility of errors in doing this forecast Keyword: Forcasting Production